2022
DOI: 10.1111/gcb.16141
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network

Abstract: In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 230 publications
(417 reference statements)
0
10
0
Order By: Relevance
“…The Sixth Scientific Assessment Report, issued by the Intergovernmental Panel on Climate Change (IPCC), notes that global climate change, caused by human activities and extreme weather and climate events, and the resultant sustained warming that has ensued in various locations, will cause more frequent and serious extreme events [1]. Compound events are generally more threatening to humans and the ecological environment than a single climate event [2,3]. In particular, compound droughts and heatwaves (CDHWs) have attracted increased attention in recent years [4][5][6][7], due to the significant impact that they can have upon society and the environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The Sixth Scientific Assessment Report, issued by the Intergovernmental Panel on Climate Change (IPCC), notes that global climate change, caused by human activities and extreme weather and climate events, and the resultant sustained warming that has ensued in various locations, will cause more frequent and serious extreme events [1]. Compound events are generally more threatening to humans and the ecological environment than a single climate event [2,3]. In particular, compound droughts and heatwaves (CDHWs) have attracted increased attention in recent years [4][5][6][7], due to the significant impact that they can have upon society and the environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the magnitude of NEE at this site is not smooth, but rather a larger jump from a range around −200 to −300 g C m −2 yr −1 to one closer to −500 g C m −2 yr −1 , which Keenan et al (2012) demonstrated is difficult to capture in models and not easily accounted for in carbon stock changes. A recent study from Beringer et al (2022) notes a few long-term (>20 years) Australian tower sites records, including a temperate mixed Eucalypt forest (AU-Tum) and a tropical savanna (AU-How). These sites experienced increasing water use efficiency with time in response to rising CO 2 and significant resilience in carbon uptake post-disturbance.…”
Section: Annual To Decadal Variability In Northern Forests and Wetlandsmentioning
confidence: 99%
“…For the first phase of RECCAP (RECCAP‐1), a carbon budget for Australia was produced for the period 1990–2011 (Haverd et al., 2013). Other studies have addressed components of the role and dynamics of Australia and New Zealand's biospheric fluxes (Baisden et al., 2001; Beringer et al., 2022; Haverd et al., 2016; Roxburgh et al., 2004; Tate et al., 2000; Teckentrup et al., 2021; Trotter et al., 2004; Trudinger et al., 2016; Wang & Barrett, 2003). In addition, recent studies have provided estimates of the net carbon balance of these countries based on global and regional atmospheric inversions (Byrne et al., 2023; Steinkamp et al., 2017; Villalobos et al., 2022).…”
Section: Introductionmentioning
confidence: 99%